Composition and Origin of the Fermentation Microbiota of Mahewu, a Zimbabwean Fermented Cereal Beverage - Pswarayi, Felicitas (Appl Environ Microbiol, 2019)
Mahewu is a fermented cereal beverage produced in Zimbabwe. This study determined the composition and origin of mahewu microbiota. The microbiota of mahewu samples consisted of 3 to 7 dominant strains of lactobacilli and two strains of yeasts. Enterobacteriaceae were not detected. Candida glabrata was present in high cell counts from samples collected in summer but not from samples collected in winter. Millet malt is the only raw ingredient used in the production of mahewu and is a likely source of fermentation microbiota; therefore, malt microbiota was also analyzed by culture-dependent and high-throughput 16S rRNA gene sequencing methodologies. Millet malt contained 8 to 19 strains of Enterobacteriaceae, lactobacilli, bacilli, and very few yeasts. Strain-specific quantitative PCR assays were established on the basis of the genome sequences of Lactobacillus fermentum FUA3588 and FUA3589 and Lactobacillus plantarum FUA3590 to obtain a direct assessment of the identity of strains from malt and mahewu. L. fermentum FUA3588 and FUA3589 were detected in millet malt, demonstrating that millet malt is a main source of mahewu microbiota. Strains which were detected in summer were not detected in samples produced at the same site in winter. Model mahewu fermentations conducted with a 5-strain inoculum consisting of lactobacilli, Klebsiella pneumoniae, and Cronobacter sakazakii demonstrated that lactobacilli outcompete Enterobacteriaceae, which sharply decreased in the first 24 h. In conclusion, mahewu microbiota is mainly derived from millet malt microbiota, but minor components of malt microbiota rapidly outcompete Enterobacteriaceae and Bacillus species during fermentation. IMPORTANCE This study provides insight into the composition and origin of the microbiota of mahewu and the composition of millet malt microbiota. Fermentation microbiota are often hypothesized to be derived from the environment, but the evidence remains inconclusive. Our findings confirm that millet malt is the major source of mahewu microbiota. By complementing culture methods with high-throughput sequencing of 16S rRNA amplicons and strain-specific quantitative PCR, this study provides evidence about the source of mahewu microbiota, which can inform the development of starter cultures for mahewu production. The study also documents the fate of Enterobacteriaceae during the fermentation of mahewu. There are concerns regarding the safety of traditionally prepared mahewu, and this requires in-depth knowledge of the fermentation process. Therefore, this study elucidated millet malt microbiota and identified cultures that are able to control the high numbers of Enterobacteriaceae that are initially present in mahewu fermentations.